Rooting of the Endemic Brazilian Species Campomanesia pubescens using Biotechnological Techniques (Plant Tissue Culture and Biotechnology, 2022)
Abstract not availablePlant Tissue Cult. & Biotech. 31(2): 173-177, 2021 (December)